Validity and reliability of the single-trial line drill test of anaerobic power in basketball players - Fatouros, I. G.; Laparidis, K.; Kambas, A.; Chatzinikolaou, A.; Techlikidou, E.; Katrabasas, I.; Douroudos, I.; Leontsini, D.; Berberidou, F.; Draganidis, D.; Christoforidis, C.; Tsoukas, D.; et al. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: This study evaluated the validity, reliability, and sensitivity of the single-trial line drill test (SLDT) for anaerobic power assessment. METHODS: Twenty-four volunteers were assigned to either a control (C, N.=12) or an experimental (BP, N.=12 basketball players) group. SLDT`s (time-to-complete) concurrent validity was evaluated against the Wingate testing (WAnT: mean [MP] and peak power [PP]) and a 30-sec vertical jump testing test (VJT: mean height and MP). Blood lactate concentration was measured at rest and immediately post-test. SLDT`s reliability [test-retest intraclass correlation coefficients (ICC), coefficient of variation (CV), Bland-Altman plots] and sensitivity were determined (one-way ANOVA). RESULTS: Kendall`s tau correlation analysis revealed correlations (P<0.05) between SLDT time and WAnT`s PP (=0.78) and MP (=0.56) and VJT`s MP (=0.85) and height (=0.90). SLDT lactate concentration was moderately (P<0.05) correlated with the respective lactate values of WAnT (=0.40) and VJT (=0.66). SLDT time in BP correlated (P<0.05) with VJT`s MP (=0.80) and height (=0.90) but not with WAnT performance variables. SLDT lactate responses in BP were moderately (P<0.05) correlated with WAnT`s PP (=0.54) and VJT MP (=0.68), height (=0.65), and lactate concentration (=0.65). ICCs for time and lactate were 0.92 and 0.93, respectively (P<0.05) although Bland-Altman plots and CV indicate that SLDT time demonstrated greater reliability than lactate responses. In all tests, BP demonstrated higher (P<0.05) performance levels compared to C indicating an adequate sensitivity for SLDT. CONCLSION: Results suggest that the SLDT appears to be a valid, reliable, and sensitive field test of anaerobic capacity for basketball players.